2003
DOI: 10.1046/j.1365-2141.2003.04148.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia and anaemia associated with T‐cell large granular lymphocyte leukaemia responds to fludarabine with minimal toxicity

Abstract: Summary. T-cell large granular lymphocyte leukaemia (T-LGL) is a clonal disorder of T cells associated with neutropenia and anaemia. The clinical consequences are recurrent infections and transfusion dependence. The optimum treatment for severely affected patients remains to be defined. Current therapies require long-term administration to maintain an effect. We report the reversal of severe neutropenia and/or anaemia in four patients treated with fludarabine which has been maintained since stopping treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 10 publications
1
29
0
4
Order By: Relevance
“…Sternberg et al reported the reversal of severe neutropenia and/or anemia in four patients treated with fludarabine [93], although the malignant clone persisted. Similar success has been reported in case reports using pentostatin [94,95].…”
Section: Natural History Prognosis and Therapy Of Lgl Leukemiamentioning
confidence: 99%
“…Sternberg et al reported the reversal of severe neutropenia and/or anemia in four patients treated with fludarabine [93], although the malignant clone persisted. Similar success has been reported in case reports using pentostatin [94,95].…”
Section: Natural History Prognosis and Therapy Of Lgl Leukemiamentioning
confidence: 99%
“…These agents should be offered to young patients, particularly when relevant bone marrow infiltration is demonstrated. Successful responses to purine analogs have been reported in the majority of patients treated with pentostatin, fludarabine and 2-chlorodeoxyadenosine, [42][43][44] but the numbers of patients treated in this way are still very low. In selected cases, mainly refractory/relapsed patients with NK disorders, more aggressive strategies might be tried, with the use of L-asparaginase-containing regimens.…”
mentioning
confidence: 99%
“…Since only few patients with LIGIV deficiency have been described, it is still unknown whether this syndrome, like NBS and ataxia teleangiectatica, is also associated with an increased cancer risk. However, the first patient with a known defect in NHEJ who was homozygous for a missense mutation in LIGIV developed an ALL at the age of 14 years (reviewed in O'Driscoll et al 4 and Girard et al 5 ). From the evidence presented above, LIGIV involved in NHEJ is a plausible candidate gene for a cancer predisposition syndrome.…”
mentioning
confidence: 99%
“…Also, fludarabine had been reported to ameliorate the cytopenias associated with T-LGL leukemia, without eradicating the leukemic clone. 4 Furthermore, fludarabine alone or combined with cyclophosphamide was reported to induce only partial remissions in T-LGL leukemia. 5 Patient 1 in our study achieved a durable remission without mitoxantrone, a response indistinguishable from cases 2 and 3 achieving CR with FND.…”
mentioning
confidence: 99%